Lime stabilization of marginal soil as capping layer for road construction [compact dics] - 304207 Mustafa Kamal Shamshuddin (Skudai : Universiti Teknologi Malaysia, 2004)
Thesis (Sarjana Kejuruteraan (Awam - Geoteknik)) -Universiti Teknologi Malaysia, 2004